Midterm Outcomes of Muscle-Preserving Posterior Lumbar Decompression via Sagittal Splitting of the Spinous Process: Minimum 5-Year Follow-up - Son, Hee Jung; Chang, Bong-Soon; Chang, Sam Yeol; Gimm, Geunwu; Kim, Hyoungmin (Clinics in orthopedic surgery, 2023)
To overcome several disadvantages of conventional laminectomy for degenerative lumbar spinal stenosis (DLSS), several types of minimally invasive surgery have been developed. The purpose of the present study was to report the clinical and radiological mid-term outcomes of spinous process-splitting decompression (SPSD) for DLSS.BackgroundTo overcome several disadvantages of conventional laminectomy for degenerative lumbar spinal stenosis (DLSS), several types of minimally invasive surgery have been developed. The purpose of the present study was to report the clinical and radiological mid-term outcomes of spinous process-splitting decompression (SPSD) for DLSS.Seventy-three consecutive patients underwent SPSD between September 2014 and March 2016. Of these, 42 (70 segments) who had at least 5 years of follow-up were analyzed retrospectively. The visual analog scale for back pain and leg pain, Oswestry disability index, and walking distance without resting were scored to assess clinical outcomes at the preoperative and final follow-up. A subgroup analysis was performed according to the union status of the split spinous processes (SPs). For radiological outcomes, slip in the neutral position as a static parameter, anterior flexion-neutral translation, and posterior extension-neutral translation as a dynamic parameter were measured before and at the final follow-up after surgery. Spinopelvic parameters were also measured. Reoperation rate at the index levels was investigated, and predictive risk factors for reoperation were evaluated using multivariate logistic regression. Survival analysis was performed with reoperation as the endpoint to estimate the longevity of the SPSD for DLSS.MethodsSeventy-three consecutive patients underwent SPSD between September 2014 and March 2016. Of these, 42 (70 segments) who had at least 5 years of follow-up were analyzed retrospectively. The visual analog scale for back pain and leg pain, Oswestry disability index, and walking distance without resting were scored to assess clinical outcomes at the preoperative and final follow-up. A subgroup analysis was performed according to the union status of the split spinous processes (SPs). For radiological outcomes, slip in the neutral position as a static parameter, anterior flexion-neutral translation, and posterior extension-neutral translation as a dynamic parameter were measured before and at the final follow-up after surgery. Spinopelvic parameters were also measured. Reoperation rate at the index levels was investigated, and predictive risk factors for reoperation were evaluated using multivariate logistic regression. Survival analysis was performed with reoperation as the endpoint to estimate the longevity of the SPSD for DLSS.All clinical outcomes improved significantly at the final follow-up compared to those at the initial visit (p < 0.05). The clinical outcomes did not differ according to the union status of the split SP. There were no cases of definite segmental instability and no significant changes in the static or dynamic parameters after surgery. Sacral slope and lumbar lordosis increased, and pelvic tilt decreased significantly at the follow-up (p < 0.05), despite no significant change in the sagittal vertical axis. The mean longevity of the procedure before the reoperation was 82.9 months. Five patients (11.9%) underwent reoperation at a mean of 52.2 months after the SPSD. There were no significant risk factors for reoperation; however, the preoperative severity of foraminal stenosis had an odds ratio of 7.556 (p = 0.064).ResultsAll clinical outcomes improved significantly at the final follow-up compared to those at the initial visit (p < 0.05). The clinical outcomes did not differ according to the union status of the split SP. There were no cases of definite segmental instability and no significant changes in the static or dynamic parameters after surgery. Sacral slope and lumbar lordosis increased, and pelvic tilt decreased significantly at the follow-up (p < 0.05), despite no significant change in the sagittal vertical axis. The mean longevity of the procedure before the reoperation was 82.9 months. Five patients (11.9%) underwent reoperation at a mean of 52.2 months after the SPSD. There were no significant risk factors for reoperation; however, the preoperative severity of foraminal stenosis had an odds ratio of 7.556 (p = 0.064).SPSD for DLSS showed favorable clinical and radiological outcomes at the mid-term follow-up. SPSD could be a good surgical option for treating DLSS.ConclusionsSPSD for DLSS showed favorable clinical and radiological outcomes at the mid-term follow-up. SPSD could be a good surgical option for treating DLSS.